(untitled) (Medical Forum Monthly, 2021)
Objective: To Study the Frequency of Proximal Migration of Ureteric Stone during Ureteroscopic Pneumonic Lithotripsy. Study Design: Descriptive / cross sectional / Experimental study Place and Duration of Study: This study was conducted at the department of Urology, Lady Reading Hospital Peshawar, from Jan 2019 to May 2020. Materials and Methods: Sample size was calculated using WHO calculator and total 160 patients were enrolled with 5% margin of error and95% confidence interval and consecutive nonprobability sampling technique was used. All patients having urinary stone of size less than or equal to 15mm, age 30-70 years and both genders were included in the study whereas all those who had previous history of ESWL, dj stent placement ,age less than 30 and > 70 were excluded from the study. After taking permission from ethical committee of the hospital, patients were admitted in the department and informed consent was taken. Detailed history and examination was performed and diagnosis was made by using x-ray KUB, Ultrasound abdomen and CTU or IVU (having normal RFTs). Data was recorded on a predesigned proforma and was analyzed using the statistical program SPSS version 20. Frequency and percentages were calculated for categorical variables like gender and stone migration. Descriptive statistics like mean ± standard deviation was calculated for numerical variable age and size of stone. Results: During the study period 160 cases (83 male and 77 female) of ureteric stones were included in the study.In total 20 (12.5%) patients proximal stone migration was observed. Conclusion: It is concluded from our study that proximal stone migration during pneumatic lithtripsy was major complication. And preventive measures were made for it.